2018
DOI: 10.1002/mame.201800450
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Cellulose Using Ionic Liquids

Abstract: The processing of cellulose dissolved in ionic liquids (ILs) enables the development of new materials. Besides the established production of cellulosic fiber products, interesting technical applications are developed like super micro filament fibers, cellulose/chitin blend fibers, precursors for carbon fibers, and all‐cellulose composites. This review provides a detailed summary of these new developments and describes how ILs are selected for the processing of cellulose with a particular emphasis on industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 91 publications
0
60
0
Order By: Relevance
“…The dissolution process of the pulp in the IL for the formation of the matrix precursor has been described earlier . Different concentrations of cellulose in the IL in the range of 3–8 wt% were used ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissolution process of the pulp in the IL for the formation of the matrix precursor has been described earlier . Different concentrations of cellulose in the IL in the range of 3–8 wt% were used ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, CMCs based on these materials suffer from poor mechanical properties as a result of the defects in the carbonaceous and molecular structure of these biogenic materials, which both negatively influence mechanical properties. Recently, we reported on all‐cellulose composites (ACCs) based on high‐strength rayon fibers embedded in a cellulose pulp matrix . These ACCs offer good mechanical properties and have lower defects in the structure, show strong fiber‐matrix interaction and are thus promising starting materials for CMCs.…”
Section: Introductionmentioning
confidence: 99%
“…Applying IL/cellulose solutions, there is a range of possibilities to process cellulose for applications other than continuous filaments or fibers. Such new developments were highlighted in a review by Hermanutz et al [ 146 ] Interesting technical applications such as all‐cellulose composites, spinning of polymer blends (e.g., cellulose plus chitin) and precursors for carbon fibers were described. [ 147 ] For carbon fiber precursors, it was shown that the use of different ILs makes it possible to co‐spin lignin (another abundant renewable wood‐based macromolecule) with cellulose.…”
Section: Regeneration Of Cellulose In Different Physical Formsmentioning
confidence: 99%
“…The tunability of anions and cations of ILs has shown great potential in the synthesis of materials, which can be used as a solvent and structure directing agent to improve the crystal form and morphology of inorganic materials in the synthesis of inorganic materials [ 52 , 53 , 54 ]. In addition, in the synthesis of organic materials, ILs can dissolve cellulose [ 55 ] and participate in organic synthesis [ 41 , 56 ] by taking advantage of its miscibility with organic matter and high solvation ability. As a green solvent and new type of reaction medium instead of traditional solvents, ILs are very easy to dissolve versatile precursors.…”
Section: Ils-contained Inorganicsmentioning
confidence: 99%